Pemanfaatan Microsoft Excel Bagi Anak Muda di Kampung Enggros, Kota Jayapura - Paranoan, Nicea Roona; Tuhumena, Lolita; Aryanto, Aryanto; Wanimbo, Efray; Ayer, Popi Ida Laila; Payapo, Muhammad Zia Ulhaq; Gultom, Ayub Sahala; Numberi, Yulindra Margaretha; Pattipeilohy, Christian Ernsz; Pirhel, Pirhel (Apik Cahaya Ilmu, 2024)
The use of Microsoft Excel is very helpful in making tables, graphs, financial reporting and so on. The tools in Microsoft Excel provide convenience to its users. However, in fact, in the era of the development of science and technology, many people are still not familiar with the use of Microsoft Excel. Especially youth in Enggros Village, Jayapura City who are still collecting data manually or in writing and also few of them can operate Microsoft Excel. This community service aims to increase hardskills related to knowledge and understanding of Microsoft Excel so that it can facilitate data processing and help in completing the performance of youth and the people of Enggros Village by utilizing Microsoft Excel. This service is in the form of socialization with stages of surveys, participant data collection, program preparation, provision of materials, training, question and answer sessions and pre-tests and post-tests are carried out for activity evaluation. The community service lasted for 2 days, with 18 participants. The evaluation results after this community service activity showed that 78% of participants knew and could operate Microsoft Excel very well and had values ​​that were in accordance with expectations.